Antioxidant and antibacterial activities of Annona muricata stem extracts - SAMREEN BANO; POONAM PRAKASH (International Journal of Pharma and Bio Sciences, 2017)
The present study aimed at in vitro study of the antioxidant and antibacterial activities of methanol, acetone and hexane extracts of Annona muricata stem by cold and hot methods. The antioxidant activity of these extracts were determined by using DPPH (1,1-Diphenyl -2-picryl hydroxyl) radical scavenging method. It was found that the crude hot extract of methanol solvent of Annona muricata stem had significantly highest antioxidant activity as compare to all other crude extracts. All extracts showed lower antioxidant activity than the standard gallic acid. The antibacterial activity of these extracts were determined by using agar well diffusion method. DMSO was used as a solvent to dissolve the extracts, Ampicillin was taken as a positive control. It was found that the bacteria (B.licheniformis and E.coli) were largely inhibited by methanol hot extract. The present study thus suggested that the use of this medicinal plant may be exploited for health supplements.